Work Stress for Covid-19 Nurses at Pelamonia Hospital Makassar City - Muhammad Akbar Salcha; Arni Juliani; Arni (Universitas Mandala Waluya, 2021)
The hospital is one of the workplaces whose activities are prone to work stress, especially for nurses who treat Covid-19 patients. Data was obtained that the Covid-19 nurses at Pelamonia TK.II Hospital was overwhelmed to handle patients who tested positive for the Corona Virus. This suppresses the psychological condition of the nurse so that it can have an impact on stress. The purpose of this study was to determine work stress from the aspects of the working period, workload, availability of PPE, and stigma on Covid-19 nurses at Pelamonia Hospital Makassar. This type of research is descriptive. The population and sample of this study were all Covid-19 nurses with a total sampling technique of 48 people. The questionnaire used is in the form of a questionnaire. Data analysis using univariate analysis. The results showed that of the 48 Covid-19 nurses who experienced mild work stress as many as 31 people (64,6%), 24 new and old work periods (50,0%), heavy workloads of 30 people (62,5%) ) and light workload as many as 18 people (37,5%), the availability of PPE as many as 43 available (89,6%) and not available as many as 5 (10,4%) and negative stigma as many as 48 people (100%). The hospital should increase the provision of complete PPE, improve management system rules regarding nurses' working time, delegate authority in the division of nursing tasks and analyze workloads according to the needs of each room.